Printing Spinoza A Descriptive Bibliography of the Works Published in the Seventeenth Century - van de Ven, Jeroen M.M (Library of the Written Word, 2022)
In this descriptive bibliography Jeroen van de Ven examines all editions of Spinoza's writings published between 1663 and 1694: his exposition of Descartes's 'Principles' with the 'Metaphysical Thoughts', the 'Theological-Political Treatise', and the posthumous writings, with the 'Ethics'.